Mandatory disclosure of standardized sustainability metrics: The case of the EU Taxonomy Regulation - Nipper, Marvin; Theis, Jochen; Ostermaier, Andreas (Corporate Social Responsibility and Environmental Management, 2024)
The European Union's Taxonomy Regulation establishes standardized sustainability metrics and makes disclosure mandatory for many companies, aiming to channel investment into sustainable business. These metrics compete with voluntary third-party sustainability ratings in influencing investors. Using an online vignette study, we examine how green revenue, as an exemplary standardized metric, interacts with a traditional third-party rating to influence investors. We find that green revenue influences investors, but sustainability ratings have an incremental effect, both if green revenue is low and if it is high. Hence, sustainability ratings remain relevant for companies and investors. Our findings contribute to the literature on real effects of reporting regulation and have important implications for mangers and regulator
Keywords: ESG reporting; EU Taxonomy; green revenue; investor decision-making; sustainability reporting